Kedudukan Hukum Akta Pengikatan Jual Beli Sebagai Jaminan Hutang-Piutang (Studi Kasus Putusan Pengadilan No. 19/PDT.G/2020/PN GPR) - Safitri Juliani, Dyana (UNES Law Review, 2023)
For parties who will enter into a debt and credit agreement that uses land rights certificates as collateral, it must be done with a mortgage right, not using a deed of Sale and Purchase Agreement. The problem in this research is to discuss the legal position of the Sale Purchase Bond Deed used as a debt and credit agreement based on Decision No. 19/PDT.G/2020/PN GPR. This research uses doctrinal research methods. The result of this research is that the position of the Sale and Purchase Agreement (PPJB) binding deed made for debt and credit settlement has violated the rule of law which contains a false and forbidden cause and is a form of legal smuggling as if there was a transfer in the form of a sale and purchase by violating the law by making a document in the form of a PPJB deed made notarially so that the position of the PPJB made for debt and credit settlement does not have legal force.